Pronunciamento judicial vinculante no Brasil: desafios e perspectivas em relação à sua interpretação e aplicação segundo as fórmulas enunciativas típicas do sistema do civil law - Moreira, Felipe Augusto de Toledo (2018)
This is a research paper in the field of Civil Procedural Law focused on the investigation of the theoretical foundations of legal opinions on judicial precedents within the scope of the common law system, as well as on the challenges and prospects faced by law professionals in the Brazilian legal system when interpreting and applying (or attempting to apply) said legal opinions based of the precedents characteristic of civil law systems. On one hand, practical objectives are sought in both legal systems, namely: legal certainty, uniformity and stability of judicial decisions, respect for the effective equality of persons under the jurisdiction of the courts and for predictability against judicial discretion. On the other hand, based on distinct legal traditions and social, political and cultural environments, one demonstrates the necessary theoretical work that is necessary to produce assumptions for the development of a true and effective Brazilian theory of binding judicial decisions, avoiding the artificial nature of the mere, detached and reckless, importation of concepts that are of no use to present society. The precedents characteristic of the civil law system, above all the precedents of Brazilian courts, whether binding or not, aim to transform the ratio decidendi into general precedents that will serve as models for future decisions. However, the slightest flaw in this process of abstraction (questioning, form the outset, whether it can be deemed useful to the present system) can give rise to disastrous consequences to the decision-making system as a whole, falsely legitimizing subverted judicial relief. A clear example of this is the mistaken interpretation and application of precedent nos. 84 and 308 of the Precedent of the Superior Court of Justice which, detached from the cases that substantiated them, bind judicial decisions in a manner that is entirely distorted, surprising the persons subject to the jurisdiction of the court and violating the principles of legality, equality and certainty, which are so dear to our legal system. The earnest study of the forms of control and of the limitations of these binding effects, having the 2015 Code of Civil Procedure as a legal framework and endeavouring to establish criteria for the proper representation of the ratio decidendi by means of general precedents (should this prove to be truly possible and beneficial to our legal system), is a necessary measure so as to shed light on the development of the formulation of a Brazilian theory of binding judicial decisions